2021
DOI: 10.1158/1055-9965.epi-20-1003
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening: Comparison of Conventional Pap Smear Test, Liquid-Based Cytology, and Human Papillomavirus Testing as Stand-alone or Cotesting Strategies

Abstract: Background: Some countries have implemented stand-alone human papillomavirus (HPV) testing while others consider cotesting for cervical cancer screening. We compared both strategies within a population-based study. Methods: The MARZY cohort study was conducted in Germany. Randomly selected women from population registries aged ≥30 years (n = 5,275) were invited to screening with Pap smear, liquid-based cytology (LBC, ThinPrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 47 publications
1
20
0
1
Order By: Relevance
“…Similar findings have been reported in previous studies. [15][16][17] When deciding which test to use for screening, both sensitivity and specificity must be taken into account because tests with low sensitivity will fail in correctly identifying precancerous lesions while tests with low specificity will result in a high proportion of false-positive test results, unnecessary procedures and associated adverse health effects. HPV-test is increasingly recognised as the preferred cervical screening method due to its high sensitivity for detection of CIN2+.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings have been reported in previous studies. [15][16][17] When deciding which test to use for screening, both sensitivity and specificity must be taken into account because tests with low sensitivity will fail in correctly identifying precancerous lesions while tests with low specificity will result in a high proportion of false-positive test results, unnecessary procedures and associated adverse health effects. HPV-test is increasingly recognised as the preferred cervical screening method due to its high sensitivity for detection of CIN2+.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study showed that the positive rate of liquid-based cytology test results increased with the increase of pathological grade. Liang et al [ 13 ] indicated that some patients with ASCUS detected by liquid-based cytology may be diagnosed with benign lesions or potential malignant changes, which cannot be clearly classified and diagnosed but can only be suggested for the presence of lesions, which is quite different from the gold standard of pathological biopsy under colposcopy. Therefore, cytological test results alone cannot be used as pathological criteria in clinical practice.…”
Section: Related Workmentioning
confidence: 99%
“…The data stem from randomly recruited participants from the general population (n = 2,627) who were screened within the randomised trial and prospective cohort MARZY study, described previously [ 27 , 28 ]. Briefly, women eligible from the general population (aged 30 to 65 years, with no history of hysterectomy or CC and not pregnant) were screened by office-based gynaecologists at study baseline (R1, 2005–2007) with routine Pap smear, plus an additional MARZY study swab (liquid-based cytology, ThinPrep, Cytyc/Hologic including subsequent HPV testing, Hybrid Capture®2).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, women eligible from the general population (aged 30 to 65 years, with no history of hysterectomy or CC and not pregnant) were screened by office-based gynaecologists at study baseline (R1, 2005–2007) with routine Pap smear, plus an additional MARZY study swab (liquid-based cytology, ThinPrep, Cytyc/Hologic including subsequent HPV testing, Hybrid Capture®2). HPV co-testing was investigated [ 27 ]. Participants were administered a questionnaire (Q1) relating to sociodemographic and other factors.…”
Section: Methodsmentioning
confidence: 99%